2018
DOI: 10.3389/fphar.2018.00776
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Surgical Site Infections: A Systematic Review of Cost Analyses in the Use of Prophylactic Antibiotics

Abstract: Introduction: The preoperative phase is an important period in which to prevent surgical site infections (SSIs). Prophylactic antibiotic use helps to reduce SSI rates, leading to reductions in hospitalization time and cost. In clinical practice, besides effectiveness and safety, the selection of prophylactic antibiotic agents should also consider the evidence with regard to costs and microbiological results. This review assessed the current research related to the use of antibiotics for SSI prophylaxis from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 71 publications
(159 reference statements)
2
47
0
4
Order By: Relevance
“…Among each individual isolated SSI was majorly caused by S. aureus and E. coli. This was in line with annual surveillance done in European countries and in other review [43,46].…”
Section: Discussionsupporting
confidence: 92%
“…Among each individual isolated SSI was majorly caused by S. aureus and E. coli. This was in line with annual surveillance done in European countries and in other review [43,46].…”
Section: Discussionsupporting
confidence: 92%
“…6 These infections incur costs, ranging between US$480 and US$22,130 per patient. 7 In addition, the European Centre for Disease Prevention and Control (ECDC) in 2011-2012 reported that SSI was the most common healthcare-associated infection with an incidence of 156.5 per 100,000 population. 8 Most concern exists about specific sites of infections, such as deep SSI (dSSI) involving infection of soft tissues of fascia and muscles with a high risk of development of sepsis as a complication.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings have been reported by other studies. [15][16][17] During the intervention phase, patients received optimized antibiotic prescriptions, with a significant mean cost reduction of $591. A major reason for this cost reduction was a significant decrease in the duration of antibiotic use in the intervention group (94.19%) compared to the baseline group (7.87%; P<0.001).…”
Section: Discussionmentioning
confidence: 99%